Monitoring Pengunaan Daya 3 Pahase Dengan Notifikasi Berbasis Telegram - Yulian Hariski; Arief Wicaksono (Jurnal JEETech, 2022)
Voltage Monitoring, current and power on the panel is a must, because with this monitoring can see the magnitude of the voltage, current, cos phi and power on the load. One of these monitoring is to find out whether the quality of electricity, such as drop voltage, low cos phi. In this era of technology, monitoring can be viewed using mobile, so users don't need to come to the panel and see the measurement results, user just look at the smartphone device. In this research, researcher will make a tool that can monitoring electrical measurements in 3 phase panel using mobile on a microcontroller. Data will processed from the current transformer at 3 phase panel by the ESP8266 microcontroller to converted into three-phase voltage, current and power figures. The ESP8266 microcontroller which is equipped with wifi can be used for remote monitoring. An android smartphone with a telegram software application will function as communication via wifi with the ESP8266 microcontroller, so that all measurement data can also be monitored on the smartphone. This shows that the tool can function very well.